Aviário sustentável: um estudo de caso aplicado em uma pequena propriedade rural familiar - Dacroce, Noeli Pedroso Dias (2017)
The poultry Industry has a relevant attribution for agribusiness in Brazil, regarding the economic and social aspect. However, given the high consumption of water and electricity, and the high generation of waste, it becomes aggressive and polluting the environment. The objective of this research is to characterize poultry of broiler chicken in terms of the interfaces of technological innovation, proposing sustainable alternatives. For the elaboration of this research, as methodology, it was based on the qualitative research approach. As for the objectives, these are classified as exploratory, descriptive and applied research. Regarding the procedures, field research was chosen. For the economic viability analysis, the techniques of Net Present Value (NPV), simple payback and discounted payback were used. As a result, the proposed photovoltaic energy installation project presented economic viability in the 18-year period for the simple payback and 19 years for the discounted payback. Since these are third-party resources (Pronaf Mais Alimentos), we opted to use the same rate applied by the Financial Institution (2.5%) as the Average Attractiveness Rate (TMA). The investment showed a Profitability Index (IL) of 17.11% during the project life and Internal Rate of Return (IRR) 3.76% per annum. The rainwater harvesting system presented economic viability in the 15-year period by simple payback and infeasibility for the 18-year period for the discounted payback, with an IRR of 4% per year and IL of (-29%). In this research, it was also identified that rainwater is of satisfactory quality for animal consumption and for human consumption. Regarding solid waste management, the property produces an average of 350 tons of poultry litter per 18 lots (2 years) and the packaging, booties, gloves and rodent poison remains totaled 1,960 kg in the analyzed period. When assessing the perception of the managers of the poultry integrators regarding sustainability and the implementation of "Sustainable Aviaries", it was identified that all managers of the companies questioned believe that Sustainable Aviaries are necessary and should be implemented in the long term. From the results presented, it is understood that rainwater harvesting system, photovoltaic power generation system and solid waste management are mechanisms that can contribute to reduce the environmental impacts caused by the poultry production process, promoting rural development sustainable development.